А) 3P + 5HNO3 + 2H2O → 3H3PO4 + 5NO P(0) - 5e = P(+5) ∫ * 1 N(+5) + 1e = N(+2) ∫ *5 P (P(0))- восстановитель HNO3 (N(+5))- окислитель б) H2S + 2HNO3 → S + 2NO2 + 2H2O S(-2) - 2e = S(0) ∫*1 - восстановитель N(+5) + 1e = N(+4) ∫*2 - окислитель в) 4HCl + O2 → 2H2O + 2Cl2 2Cl (-1) - 2e = Cl2 (0) ∫*2 - восстановитель O2 (0) + 4e = 2O (-2) ∫ *1 - окислитель г) 2H2S + 3O2 → 2SO2 + 2H2O S(-2) -6e = S(+4) ∫*2 - восстановитель O2(0) -4e = 2O(-2) ∫*3 - окислитель
O2(0) +4e = 2O(-2) ∫*3 - окислитель случайно написал - вместо +